Real-world data from a molecular tumor board demonstrates improved outcomes with a precision N-of-One strategy - Shumei Kato (Nature Portfolio, 2020)
A molecular tumor board (MTB) is often used as a platform that integrates clinical and molecular parameters for clinical decision making. Here, the authors review the outcome of 715 cancer patients presented at their institution’s MTB, and demonstrate that patients who received a MTB-recommended regimen received therapy that was better matched to their alterations and achieved better clinical outcomes.